The effect of Pentazocin to anta gonise respiratory depression due to Fentanyle during general anesthesia - Rahmani Ghods (Iran University of Medical Sciences, 1999)
This experimental study was done in order to determine the effect of Pentozocin to antagonise respiratory   depression due to Fentanyle during general anesthesia in selected hospitals of the Medical Science University of Iran and Tehran.   Subjects of this study consisted of 50 patients who were chosen randomly, and divided into two group of 25   each. Group one received pentazocine before the end of general anesthesia but group two did not.   The method use to collect data in this study consisted of a check list and questionnaire. the check list included   questions related to demographic characteristics of subjects and the questionnaire consisted of 4 items related to the respiratory rate. before the end of general anesthesia and also before extubation by endothracheal Tube.